The role of interleukin‐22 in pityriasis rosea. (1st January 2017) - Al Mokadem, S.; Ghonemy, S.; Zidan, A.; Abd El Aleem, G.
Summary: Background: Pityriasis rosea (PR) is an exanthematous disease related to reactivation of human herpes virus (HHV) types 6 and 7. The pathogenesis and cytokine profile of PR are still poorly understood.There is a large amount of evidence indicating a viral aetiology for PR. Aim: To measure the serum level of interleukin (IL)‐22, a cytokine expressed by T helper (Th)17 cells in patients with PR to explore the possible association of IL‐22 with the pathogenesis of the disease. Methods: This case–control study enrolled 25 patients with PR (mean ± SD age 20 ± 12 years) and a control group of 25 apparently healthy individuals (mean age 18 ± 12.1 years). Blood samples were collected from both patients and controls to measure serum IL‐22. Scoring of PR was performed using the Pityriasis Rosea Severity Score (PRSS). Results: There was a statistically significant difference in IL‐22 serum level between the patient and control groups. The IL‐22 serum level increased with increase in disease severity (PRSS), extent and duration. Conclusion: Through its proinflammatory cytokines, IL‐22 plays a role in the inflammatory process of PR.